Recombinant fibronectin polypeptide antagonizes hepatic failure induced by endotoxin in mice - WU Yong; CHEN Yuan-zhong; HUANG Hui-fang; CHEN Ping (Acta Pharmacologica Sinica, 2016)
AIM: To study the preventive effect of recombinant human fibronectin (rhFN) polypeptide on hepatic failure induced by endotoxin in mice. METHODS: A cDNA fragment coding for Ile1363-Tyr1725 of human FN was inserted into the PinPoint Xa-3 plasmid, and the constructed plasmid was transformed into E coli BL21 (DE3) cells, and then the expression of rhFN polypeptide in DE3 cells was identified through SDS-PAGE. The target protein from the supernatant of bacteria lysate was purified through biotin-affinity chromatography. The bioactivity of the purified rhFN polypeptide was determined with cell adhesive activity. The survival rate was observed in endotoxemia mice injected with rhFN polypeptide. The tissue damage in hepatocyte was detected using histology, ultrastructure, and DNA fragmentation assay. RESULTS: The expression of rhFN polypeptide reached approximately 20 % of the total cellular protein. The adhesion ability of rhFN polypeptide was concentration-dependent. The value of EC(50) was 0.8 nmol/L. The survival rate of endotoxemia mice sensitized by D-galactosamine (D-GalN) was 60 % in rhFN polypeptide treated group, while that of endotoxemia mice sensitized by D-GalN was 20 % in the control group (P